The development and validation of the Satisfaction Questionnaire for Osteoporosis Prevention in Malaysia - Toh, Li Shean (Dove Medical Press, 2014)
PURPOSE: To develop and validate the English version of the Satisfaction Questionnaire for Osteoporosis Prevention (SQOP) in Malaysia. METHODS: The SQOP was modified from the Osteoporosis Patient Satisfaction Questionnaire and developed based on literature review and patient interviews. Face and content validity were established via an expert panel. The SQOP consists of two sections: clinical services and types of counseling. There were 23 items in total, each with a five-point Likert-type response. Satisfaction score was calculated by converting the total score to a percentage. A higher score indicates higher satisfaction. English speaking, non-osteoporotic, postmenopausal women aged ≥50 years were included in the study. Participants were randomized to either the control or intervention group. Intervention participants were provided counseling, whereas control participants received none. Participants answered the SQOP at baseline and 2 weeks later. RESULTS: A total of 140 participants were recruited (control group: n=70; intervention group: n=70). No significant differences were found in any demographic aspects. Exploratory factor analysis extracted seven domains. Cronbach’s α for the domains ranged from 0.531–0.812. All 23 items were highly correlated using Spearman’s correlation coefficient 0.469–0.996 (P<0.05), with no significant change in the control group’s overall test–retest scores, indicating that the SQOP achieved stable reliability. The intervention group had a higher score than the control group (87.91±5.99 versus 61.87±8.76; P<0.05), indicating that they were more satisfied than control participants. Flesch reading ease was 62.9. CONCLUSION: The SQOP was found to be a valid and reliable instrument for assessing patients’ satisfaction towards an osteoporosis screening and prevention service in Malaysia.